2006
DOI: 10.1080/10245330600775105
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency in childhood and adolescence: Retrospective review

Abstract: Two hundred and thirty-eight subjects of both sexes, age range 7.5 months-16 years, with iron deficiency (ID), were included in a retrospective review of ID causes, to determine the best treatment. Inadequate iron intake was the cause of ID or iron deficiency anemia (IDA) in 59 subjects from the first months of life to adolescence. Blood loss linked to cow's milk intolerance was the cause of ID or IDA in 37 younger children. Meckel's diverticulum (MD) (6 cases), reflux esophagitis (RE) (10 cases), some drugs s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 15 publications
2
32
0
Order By: Relevance
“…1 ID can be caused by diverse pathogenetic mechanisms, such as nutritional deficiencies, impaired iron absorption, and blood loss. 8,[12][13][14][15][16][17][18]20 This study showed that the main mechanisms were distinct for different age groups. Premature and low birth weight infants have a high risk for ID because of low iron content at birth and poor oral iron intake.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 ID can be caused by diverse pathogenetic mechanisms, such as nutritional deficiencies, impaired iron absorption, and blood loss. 8,[12][13][14][15][16][17][18]20 This study showed that the main mechanisms were distinct for different age groups. Premature and low birth weight infants have a high risk for ID because of low iron content at birth and poor oral iron intake.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori infection was defined as a positive culture or both positive results of a rapid urea test, 13 C-urea breath test, or histology. Meckel diverticulum was confirmed by Meckel diverticulum scan or exploratory laparoscopy.…”
Section: Diagnosis Of Pathologic Etiology For Id and Idamentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly true for adolescent girls due to menstrual losses [3,4]. In addition to inadequate intake, factors which could influence iron status include strenuous exercise, pregnancy, low socioeconomic status and ethnicity, as well as disease-induced malabsorption and chronic blood loss [5] or polymenorrhea in girls [6,7]. Prevalence estimates of iron deficiency (ID) in adolescent girls range from 9 to 40%, depending on the population studied and the criteria used to define ID [8].…”
Section: Introductionmentioning
confidence: 99%